2015
DOI: 10.3923/ajas.2015.454.459
|View full text |Cite
|
Sign up to set email alerts
|

On Station Growth Performance of Crossbred Goats (Boer X Central Highland) at Sirinka, Ethiopia

Abstract: The study was conducted to evaluate the growth performance of Boer-Central Highland Goats (CHG) cross kids at Sirinka Agriculture Research Center SARC. A total of 510 kids were used for the analysis of least square mean of birth weight, weaning weight, six month weight and yearling weight. The overall least square mean of birth weight, weaning weight, six month weight and yearling weight were 2.68±0.02, 9.82±0.17, 13.54±0.20 and 19.53±0.38 kg, respectively. The body weight gained from birth to weaning, weaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 2 publications
6
8
0
Order By: Relevance
“…The faster growth rate of single-born kids than multiple-born kids during the pre-weaning period (WG1) and lower or similar performance afterward is consistent with Deribe et al (2015) and Mohammadi et al (2012) who reported that multiple-born kids gained the least weight during the pre-weaning period, but not during the post-weaning period. Competition for uterine space during pregnancy and milk after parturition could explain the reduced growth rate of multiple-born kids during pre-weaning.…”
Section: Weight Gainsupporting
confidence: 80%
See 1 more Smart Citation
“…The faster growth rate of single-born kids than multiple-born kids during the pre-weaning period (WG1) and lower or similar performance afterward is consistent with Deribe et al (2015) and Mohammadi et al (2012) who reported that multiple-born kids gained the least weight during the pre-weaning period, but not during the post-weaning period. Competition for uterine space during pregnancy and milk after parturition could explain the reduced growth rate of multiple-born kids during pre-weaning.…”
Section: Weight Gainsupporting
confidence: 80%
“…In Ethiopia, however, there is a scarcity of information. Few pieces of research have reported growth performance of 50% Boer level or F1 crossbred goats ( Belay et al., 2014 ; Deribe et al., 2015 ), and little is known about the influence of factors and their interactions on the growth and Kleiber ratio for different levels of Boer goat. Therefore, this study aims to evaluate the growth and efficiency-related traits and to identify genetic and non-genetic factors affecting the performance of different levels of crossbred goats.…”
Section: Introductionmentioning
confidence: 99%
“…The fourth finding was that mean BW of Boer crossbreds were higher than mean BW of indigenous goats, as reported elsewhere (Deribe et al 2015;Kalenga et al 2015), but smaller than the 28.7 kg theoretically expected in the absence of heterosis. This theoretical value was obtained by averaging the weight of our indigenous goats (22.3 ± 4.1 kg) and the weight of pure Boer goats raised under extensive humid tropical conditions (35.1 ± 1.32 kg) as reported by Nguluma et al (2013).…”
Section: Animal Characteristicssupporting
confidence: 72%
“…This theoretical value was obtained by averaging the weight of our indigenous goats (22.3 ± 4.1 kg) and the weight of pure Boer goats raised under extensive humid tropical conditions (35.1 ± 1.32 kg) as reported by Nguluma et al (2013). Similarly, a small BW increase was reported for crossbred goats in Ethiopia (Deribe et al 2015): they stated that birth and weaning weights of Boer crossbreds were significantly higher than weights of local breeds, but the difference dwindled as the age of kids advanced. These observations may be explained by the management conditions not allowing animals to express their genetic potential (e.g.…”
Section: Animal Characteristicsmentioning
confidence: 74%
“…In Ethiopia, researches undertaken on goat reproductive performance were largely based on single trait, often used as part of a breed performance evaluation program on research stations (Belay et al 2014 ; Solomon et al 2014 ; Deribe et al 2015 ). However, technological solutions developed through conventional station-based agricultural research have failed to achieve the expected results in the small-scale farming sector of the developing world (Stroud et al 2000 ).…”
Section: Introductionmentioning
confidence: 99%